THE MEDIATING ROLE OF WORK ENGAGEMENT: ORGANIZATIONAL CULTURE AND QUALITY OF WORK LIFE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Rismasari, Nurul; Talkah, Abu; Askafi, Eka (Jurnal Manajemen Terapan dan Keuangan, 2026)
Abstract This research aims to examine and evaluate the impact of organizational culture and quality of work life on organizational citizenship behavior via work engagement, both directly and indirectly. A saturated sampling technique was applied in this study, implying that all members of the population were included in the sample, consisting of 68 civil servants working at the Department of Communication and Informatics of Nganjuk Regency. Data were gathered via Likert-scale questionnaires and processed using SEM-PLS supported by SmartPLS 4. The study demonstrates that organizational culture and quality of work life contribute positively and significantly to employees’ work engagement. Moreover, organizational culture and work engagement positively and significantly affect organizational citizenship behavior. However, quality of work life is not significantly related to organizational citizenship behavior. However, work engagement serves as a full mediator in the link between quality of work life and organizational citizenship behavior and as a partial mediator in the effect of organizational culture on organizational citizenship behavior.  Keywords: organizational culture, quality of work life, organizational citizenship behavior, work engagement